Protecting privacy using decentralise business applications - Seah, Xin Xuan (Nanyang Technological University, 2022)
Although centralized data infrastructure such as Facebook, Google, and Amazon are primarily beneficial, it comes at the expense of the users’ privacy. Many centralized monopolies are using our data without users’ explicit permission. In cases where monopolies do ask for consensus, users usually do not have enough leverage to have a say in how their data is utilized. Compromised data security is also prominent and unavoidable in this centralized data infrastructure. Thus the purpose of this project is to showcase how decentralized web applications can be applied to free users from control and interference by any single authority.